Suppression of stall on high-camber flap using upper-surface blowing - Fang, Li (Cranfield University, 2011)
For many years, high-lift devices of an aeroplane have been employed to enhancing the aerodynamic performance of the wing during take-off and landing. But their complex geometries not only increase the design and manufacture cost, but also result in lower maintainability and reliability. Further more, they have been thought to be a major noise source of civil airliners. As one of the possible solutions, single-slot variable-camber flap design can greatly decrease the system complexity and the design cost of the high-lift system. However, the deteriorated stall behaviour of the flap prevents this concept to obtain its full benefits at high flap deflection angle. Cont/d.